Case Report: The effect of asplenia on the response to influenza vaccination and passive transfer of immunity in an adult female pig - Michael C. Rahe; John J. Byrne; Danielle Meritet; Erika Gruber; Stephanie N. Langel; Elisa Crisci (Frontiers in Immunology)
Asplenia is an important cause of morbidity and mortality in humans. However, there are only very rare examples of this condition reported in domesticated species. Here we present a case of asplenia, diagnosed at necropsy, in a crossbred adult female pig from an influenza vaccine study. The humoral antibody response, including immune response to an influenza A virus vaccine, was characterized and compared to a parity-matched pig from the same study. The antibody profiles, lower total IgM with similar levels of IgG, were remarkably similar to those described in human patients with asplenia. However, in response to vaccination, the asplenic pig showed a robust hemagglutinin-specific IgM response with lower levels of IgG and IgA. These results were mirrored in the passively transferred antibody profiles of the asplenic dam’s piglets. This constitutes the first case of congenital asplenia described in the pig.